Effect of postactivation potentiation on swimming starts in international sprint swimmers - Kilduff, L. P.; Cunningham, D. J; Owen, N. J.; West, D. J.; Bracken, R. M.; Cook, C. J. (The Journal of Strength and Conditioning Research, 2011)
The aim of this study was to investigate the effects of postactivation potentiation (PAP) on swim start performance (time to 15 m) in a group of international sprint swimmers. Nine international sprint swimmers (7 men and 2 women) volunteered and gave informed consent for this study, which was approved by the university ethics committee. Initially, swimmers performed a countermovement jump (CMJ) on a portable force platform (FP) at baseline and at the following time points 15 seconds, 4, 8, 12, and 16 minutes after a PAP stimulus (1 set of 3 repetitions at 87% 1 repetition maximum [RM]) to individually determine the recovery time required to observe enhanced muscle performance. On 2 additional days, swimmers performed a swim start to 15 m under 50-m freestyle race conditions, which was preceded by either their individualized race specific warm-up or a PAP stimulus (1 set of 3 repetitions at 87% 1RM). Both trials were recorded on 2 cameras operating at 50 Hz with camera 1 located at the start and camera 2 at the 15-m mark. Peak vertical force (PVF) and peak horizontal force (PHF) were measured during all swim starts from a portable FP placed on top of the swim block. A repeated measures analysis of variance revealed a significant time effect with regard to power output (PO) (F = 20.963, p < 0.01) and jump height (JH) (F = 14.634, p < 0.01) with a paired comparison indicating a significant increase in PO and JH after 8 minutes of recovery from the PAP stimulus. There was a significant increase in both PHF and PVF after the PAP stimulus compared to the swim-specific warm-up during the swim start (PHF 770 ± 228 vs. 814 ± 263 N, p = 0.018; PVF: 1,462 ± 280 vs. 1,518 ± 311 N, p = 0.038); however, time to 15 m was the same when both starts were compared (7.1 ± 0.8 vs. 7.1 ± 0.8 seconds, p = 0.447). The results from this study indicate that muscle performance during a CMJ is enhanced after a PAP stimulus providing adequate recovery (?8 minutes) is given between the 2 activities. In addition, this study demonstrated that swimmers performed equally well in terms of time to 15 m when a PAP stimulus was compared to their individualized race specific warm-up and indicates that PAP may be a useful addition to a warm-up protocol before races. However, more research is required to fully understand the role PAP plays in swim performance.